An investigation into the fire regimes of the upper Tsitsa River catchment - Snyman, Gareth (Rhodes University, Faculty of Science, Department of Geography, 2020)
South African grasslands are rich in flora and fauna and are a dominant vegetation cover in many of the water catchment areas, while providing a multitude of services to local communities and the environment. Fires have been the primary tool used to manage grasslands for livestock production for many years. However, there is debate about how they impact and alter landscapes and there are two schools of thought throughout literature. One argument is that fires are detrimental to landscapes; altering hydrological processes by causing excess soil erosion and changing soil properties. The other opinion is that fires are beneficial to ecosystems; maintaining vegetation structure, preventing bush encroachment, cycling nutrients and allowing for new plant growth. This study focused on the effects of fire regimes on soil properties in order to better understand the role that fire plays in geomorphic processes in the upper Tsitsa River catchment. The catchment falls under two land management types- commercial and communal, with the latter being severely degraded. Fire regimes were determined using a combination of Landsat and MODIS remotely sensed data and testing was carried out on soils exposed to different Fire Return Intervals (FRI). It was found that soils that were exposed to a high fire frequency (1-2-year FRI) exhibited a significantly higher degree of water repellency (p< 0.001) and surface hardness (p< 0.001) than soils that were exposed to a low fire frequency (3-4 year FRI), which indicates increased erosion potential. However, whilst a higher fire frequency resulted in altered soil characteristics, it contributed to landscape degradation as suggested in the literature, and soils are able to return to their previous state in over a short period of time. Further investigation into factors affecting fire regimes found that geology influenced vegetation type, resulting in differences in biomass in the two land management areas. The commercially managed land supported a high biomass, which resulted in a more natural fire regime with frequent fires, whilst the communally managed land supported less biomass. Smaller fuel loads and increased landscape fragmentation through overgrazing and road networks resulted in an altered fire regime with less frequent fires. Although the communally managed land has an altered fire regime, this research suggests that fires are not influencing the severe degradation present in these areas, and this is rather a function of geology and mismanagement of land. Whilst fire and grazing management plans can be implemented to alter the modified fire regime in the communal areas back to its natural state, this would take a long time and an increase in fires would pose a threat to surrounding communities. Overall the fire regimes in the upper Tsitsa River catchment are being altered by human influence and land management type, and whilst fire frequency is negatively altering soil properties, these soils can return to their natural state. The severe land degradation present in the communally managed areas are not a function of fire frequency and rather of geology and land management.
Keywords: Prescribed burning -- Environmental aspects -- South Africa; Fire ecology -- South Africa; Tsitsa River catchment (South Africa); Soil erosion -- South Africa; Grasslands -- Management -- South Africa